Heritability of nervous system tumors: a sibling-based design - Tettamanti, Giorgio; Kuja-Halkola, Ralf; Lavebratt, Catharina; Talbäck, Mats; Viktorin, Alexander; Scheurer, Michael E.; Feychting, Maria; Adel Fahmideh, Maral (Frontiers in Oncology, 2024)
Background The contribution of genetic and environmental factors to susceptibility to nervous system tumors remains unclear. We performed a quantitative genetic study using a sibling design to estimate the heritability of nervous system tumors, as well as the proportion of the risk of these tumors, which is attributable to environmental factors. Methods We conducted a population-based cohort study using Swedish National Register data. All individuals born in Sweden during 1950–2010 with available information on both biological parents were included. A Multi-Generation Register was used to identify family clusters, including both full- and half-siblings. Initially, one index person was randomly selected from each cluster containing only full siblings and one sibling was randomly assigned to this index person. Subsequently, within each of the remaining clusters of full- and half-siblings, an index person was randomly selected, and a half-sibling was randomly assigned to this index person. Among the randomly selected siblings, cases of nervous system tumors were identified using the cancer registry. Quantitative genetic models were used to estimate the proportion of the variance in nervous system tumors attributable to additive genetic factors, shared environment, and individual-specific environment. Results The heritability of nervous system tumors was estimated to be 29% (95% confidence interval (CI) = 19%–39%), while the contribution of the non-shared environment to the variance of nervous system tumors was estimated to be 71% (95% CI = 61%–81%). The shared environmental parameter was estimated as zero in the full model. Conclusion The variation in susceptibility to nervous system tumors is predominantly attributable to non-shared environmental factors, followed by genetic factors.